Stopping Smoking During Pregnancy: Are We on the Right Track? - Paterson, J. Michael (Can J Public Health, 2003)
BACKGROUND: Recent data suggest that although smoking during pregnancy has declined in North America, this has more to do with falling rates of smoking initiation among women of childbearing age than with increased rates of pregnancy-related smoking cessation. One possible explanation is poor exposure to effective stop-smoking strategies. Better information about women who smoke during pregnancy may help target these interventions more effectively. METHODS: The study was a cross-sectional, self-administered survey of a consecutive sample of 916 (40.4% of eligible) women who delivered healthy babies in 1997–98 at a tertiary teaching hospital in Hamilton, Ontario. Our main focus was on health behaviours (smoking, drinking, eating, and exercise habits) before and during pregnancy; but we also included questions about the presence of (other) children and (other) smokers in the household, perceived health status, the subject’s age and level of education, and whether or not the present pregnancy was planned. Factors associated with pregnancy-related smoking cessation were identified using multiple logistic regression. RESULTS: Respondents were better educated and healthier, but smoked at rates similar to women of childbearing age in Hamilton at the time of the survey. Two thirds of prior smokers or 20% of respondents overall continued to smoke during pregnancy. After adjustment for other factors, three factors were associated with ongoing smoking during pregnancy: having other smokers in the household; having other children in the household; and not having post-secondary education. CONCLUSIONS: Many pregnant smokers are not being reached by current stop-smoking strategies. New ways to help these women and their partners are needed.